Adequate (Non)Provocation and Heat of Passion as Excuse Not Justification - Fontaine, Reid Griffith (2009)
For a number of reasons, including the complicated psychological makeup of reactive homicide, the heat of passion defense has remained subject to various points of confusion. One persistent issue of disagreement has been the justificatory versus excusatory nature of the defense. In this Article, I highlight and categorize a series of varied American homicide cases in which the applicability of heat of passion was supported although adequate provocation (or significant provocation by the victim) was absent. The cases are organized to illustrate how common law heat of passion may apply in instances in which there is no actual provocation or the source of provocation is the victim. The rationale is that the emotional disturbance that interferes with one's rationality and self-control arises as an effect of the genuine belief that one has been seriously wronged, a perspective that can only be characterized as an excuse. In addition, I discuss how the rationale that this defense is a partial justification fails even in most situations in which the killer has really been seriously provoked by the victim. Finally, I clarify discrete psychological components of heat of passion homicide, and discuss how scholarly and judicial blurring of these forms of mental functioning may contribute to the longstanding confusion as to the nature of the defense. In sum, this Article contributes further evidence as to why it is correct to view heat of passion as a partial excuse